Recycling waste biosolids to forest propagation of Pinus leiophylla Schltdl. & Cham - Pedro Sinai Rivera-Torres; Jorge Flores-Velázquez; Miguel Ángel López-López; Abdul Khalil-Gardezi; Carlos Ramírez-Ayala; Erickson Basave-Villalobos (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Analyze the use of biosolids, mixed with substrates, as an alternative in the nursery and field production of forest species such as Pinus leiophylla.